Nanoscale Structure and Dynamics of Model Membrane Lipid Raft Systems, Studied by Neutron Scattering Methods - Ahmadi, Delaram; Thompson, Katherine C.; García Sakai, Victoria; Schweins, Ralf; Moulin, Martine; Haertlein, Michael; Strohmeier, Gernot A.; Pichler, Harald; Forsyth, V. Trevor; Barlow, David J.; Lawrence, M. Jayne; Foglia, Fabrizia (Frontiers in Physics, 2022)
Quasi-elastic neutron scattering (QENS) and small angle neutron scattering (SANS), in combination with isotopic contrast variation, have been used to determine the structure and dynamics of three-component lipid membranes, in the form of vesicles, comprising an unsaturated [palmitoyl-oleoyl-phosphatidylcholine (POPC) or dioleoyl-phosphatidylcholine (DOPC)], a saturated phospholipid (dipalmitoyl-phosphatidylcholine (DPPC)), and cholesterol, as a function temperature and composition. SANS studies showed vesicle membranes composed of a 1:1:1 molar ratio of DPPC:DOPC:cholesterol and a 2:2:1 molar ratio of DPPC:POPC:cholesterol phase separated, forming lipid rafts of ∼18 and ∼7 nm diameter respectively, when decreasing temperature from 308 to 297 K. Phase separation was reversible upon increasing temperature. The larger rafts observed in systems containing DOPC are attributed to the greater mis-match in lipid alkyl chains between DOPC and DPPC, than for POPC and DPPC. QENS studies, over the temperature range 283–323K, showed that the resulting data were best modelled by two Lorentzian functions: a narrow component, describing the “in-plane” lipid diffusion, and a broader component, describing the lipid alkyl chain segmental relaxation. The overall “in-plane” diffusion was found to show a significant reduction upon increasing temperature due to the vesicle membranes transitioning from one containing rafts to one where the component lipids are homogeneously mixed. The use of different isotopic combinations allowed the measured overall reduction of in-plane diffusion to be understood in terms of an increase in diffusion of the saturated DPPC lipid and a corresponding decrease in diffusion of the unsaturated DOPC/POPC lipid. As the rafts are considered to be composed principally of saturated lipid and cholesterol, the breakdown of rafts decreases the exposure of the DPPC to cholesterol whilst increasing the exposure of cholesterol to unsaturated lipid. These results show the sensitivity of lipid diffusion to local cholesterol concentration, and the importance of considering the local, rather that the global composition of a membrane when understanding the diffusion processes of lipids within the membrane. The novel combination of SANS and QENS allows a non-intrusive approach to characterize the structure and dynamics occurring in phase-separated model membranes which are designed to mimic the lateral heterogeneity of lipids seen in cellular membranes–a heterogeneity that can have pathological consequences.